2006
DOI: 10.1021/ie050839t
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation into the Chemistry Induced by Hydrodynamic Cavitation

Abstract: The chemical effects induced by acoustic cavitation (popularly known as sonochemical effects) in aqueous medium are well-known and are attributed to the production of various radicals during bubble collapse. Under the influence of pressure variation due to acoustic wave, the bubble expands with the evaporation of water at the gas-liquid interface. This water vapor condenses at the gas-liquid interface during compression. At the final moments of bubble collapse, the dynamics of bubble motion is far more rapid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 33 publications
2
85
0
1
Order By: Relevance
“…We refer the reader to our earlier article for a review of these studies. 31 We have used the diffusion limited ordinary differential equation (ODE) model using boundary layer approximation proposed by Toegel et al for our analysis, 32 which is based on the comprehensive PDE model of Storey and Szeri, 22 who showed that vapor entrapment in the cavitation bubble, leading to formation of radicals is essentially a diffusion limited process. Large amount of evaporation occurs at the bubble interface during the expansion phase of bubble motion, and vapor molecules enter and diffuse toward the bubble core.…”
Section: Bubble Dynamics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer the reader to our earlier article for a review of these studies. 31 We have used the diffusion limited ordinary differential equation (ODE) model using boundary layer approximation proposed by Toegel et al for our analysis, 32 which is based on the comprehensive PDE model of Storey and Szeri, 22 who showed that vapor entrapment in the cavitation bubble, leading to formation of radicals is essentially a diffusion limited process. Large amount of evaporation occurs at the bubble interface during the expansion phase of bubble motion, and vapor molecules enter and diffuse toward the bubble core.…”
Section: Bubble Dynamics Modelmentioning
confidence: 99%
“…Although calculating the composition of the bubble at the time of collapse, we assume that thermodynamic equilibrium is attained. 31 The equilibrium mole fraction of the various species in the bubble at the conditions of temperature and pressure at first the compression of the …”
Section: Estimation Of Physical and Chemical Effects Of Cavitationmentioning
confidence: 99%
“…It has to be noted that the hydrodynamic phenomena caused by HC are modelled by the complex hydraulic models and is the subject of numerous past and current research. [33][34][35] The description herein is provided solely for the readers to conceive the matter in an easier way. At the throat of the constriction the calculated v was approx.…”
Section: Influence Of Hc On Hydrodynamic and Photolytic Conditionsmentioning
confidence: 99%
“…Transport of solvent vapor in the bubble during radial motion, and its entrapment in the bubble at the moment of transient collapse leads to formation of radicals through thermal dissociation of the vapor molecules. Greater details on this model can be found in our previous papers (Krishnan et al, 2006;Sivasankar et al, 2007), as well as in the original papers (Toegel et al, 2000;Toegel and Lohse, 2003). For the convenience of the readers, essential equations and thermodynamic data of this model have been given in Tables S.1 and S.2 in the supplementary material.…”
Section: Model For Cavitation Bubble Dynamicsmentioning
confidence: 99%